(untitled) (International Journal of Engineering and Computer Science, 2017)
Evolution of Smart phones and their applications takes one of the important roles in pervasive computing environments. But the diversity of mobile platforms and their APIs increase the effort of software development approach for Smartphone applications. The cross-platform mobile development tool provides code less futures, but they cannot able to solve the device fragmentation issues. The purpose of this paper is to construct a robust architecture of smart phone application development, which should provide an optimal GUI solution (coherency) with the assistance of responsive functio